2009
DOI: 10.1159/000199456
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Gallbladder Stone Formation Is Increased in Patients with Predialysis Chronic Kidney Disease but Not Those Undergoing Chronic Hemodialysis Therapy

Abstract: Background: It is unclear whether the prevalence of gallbladder stones (GBS) is higher in patients with chronic kidney disease (CKD). Methods: A total of 398 patients with CKD of each of the 5 disease stages [CKD1: 26; CKD2: 52; CKD3: 58; CKD4: 48; CKD5: 214, of whom 61 were predialysis and 153 were on dialysis (CKD5D)] were included in this study. Those in whom GBS were detected by ultrasonographic examination or who had a history of cholecystectomy owing to GBS were considered GBS patients. Results: In compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
(30 reference statements)
1
16
1
Order By: Relevance
“…It has a prevalence of 10-20% in adult populations (2). In patients with chronic kidney disease (CKD), the prevalence of gallbladder stone (GBS) is shown to be increased with the advancement of disease stage, from 7.7% in CKD stage 1 to 21.3% in CKD stage 5 (3). Studies in dialysis patients showed a wide range of prevalence of GBS between 3.85%-33.3% (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…It has a prevalence of 10-20% in adult populations (2). In patients with chronic kidney disease (CKD), the prevalence of gallbladder stone (GBS) is shown to be increased with the advancement of disease stage, from 7.7% in CKD stage 1 to 21.3% in CKD stage 5 (3). Studies in dialysis patients showed a wide range of prevalence of GBS between 3.85%-33.3% (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In this study group, more than 50% of the patients are diabetic. In contrast to the general literature, Kazama et al argue that the risk of gallstone formation is higher in ESRD population except stage 5 than non-ESRD population [15].…”
Section: Discussionmentioning
confidence: 83%
“…We conclude that in general, uremic bleeding which is widely known, is well-controlled with HD treatment thus bleeding tendency should not be a major problem. Similarly, bleeding is not a problem in CAPD patients in LC [15].…”
Section: Discussionmentioning
confidence: 97%
“…69 Interestingly, the risk of gallstone formation is higher in patients before dialysis but not those undergoing chronic hemodialysis therapy, and in patients with renal transplant than those without transplant. 18,19 However, Badalamenti et al 70 reported the presence of gallstone in 28% of 119 patients on regular dialysis treatment and no relationships were found between gallstones and age or modes of dialysis. Therefore, screening for renal stone and gallstone disease during renal disease may allow early diagnosis and management.…”
Section: Relevance Of Renal and Gallstones In Renal Failurementioning
confidence: 99%
“…Furthermore, the risk of gallstone formation is higher in patients before dialysis. 18 Interestingly, Park et al 19 showed that the risk of gallstone formation is higher in patients with renal transplant than those without transplant. Although further population studies are needed, it is possible to suggest that the presence of gallstone may suggest the need to check for renal stone disease and chronic kidney disease.…”
Section: Introductionmentioning
confidence: 99%